Students’ Perspectives on DeepSeek as a Learning Aid for Enhancing English Writing Skills - Maharani Sofha Nabilla; Yeni Rahmawati; Dzul Rachman (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
In today’s digital era, students are constantly seeking new ways to improve their academic writing, especially in learning English as a Foreign Language (EFL). One tool gaining attention nowadays is DeepSeek, an AI-powered writing assistant that helps students organize ideas, correct grammar, and improve writing quality. While tools like Grammarly and ChatGPT have been widely researched, studies on students’ views of DeepSeek are still limited. This research explores students’ perspectives on using DeepSeek to improve their English writing skills. A mixed-methods approach was used, involving 55 second-semester English Education students from Universitas Muhammadiyah Kalimantan Timur who completed a questionnaire. Five students were then selected for in-depth interviews. The results show that students generally view DeepSeek as a helpful and easy-to-use tool that increases their confidence and motivation in writing. Many students reported improvements in grammar and spelling checks. However, some students raised concerns about becoming too dependent on AI and noted that DeepSeek sometimes lacks context in its corrections. The study implies that AI tools like DeepSeek can be valuable for supporting writing development in EFL learners. Still, students should be guided to use these tools wisely as assistance, not as a replacement for their thinking. A key limitation of this study is its small and localized sample, which may not reflect broader educational settings. Future research with larger and more diverse participants is recommended to better understand the wider impact of AI writing tools.